Faktor-faktor yang Mempengaruhi Keberhasilan Terapi Pasien Kusta - Sagia, Nabilla Alsa; Anggraini, Dwi Indria; Wulan, Anggraeni Janar; Sibero, Hendra Tarigan (CV. Jasa Sukses Abadi, 2024)
Leprosy is a chronic granulomatous infectious disease caused by the obligate intracellular bacterium Mycobacterium leprae (M. leprae). This disease comes from the Latin word